The nexus between financial performance and equilibrium: Empirical evidence on publicly traded companies from the global financial crisis up to the COVID-19 pandemic - Larissa Batrancea (Journal of Risk and Financial Management, 2021)
Financial performance and financial equilibrium are two key aspects that should be monitored by any business manager interested in passing the test of time and overcoming unpredictable events such as economic crises. The organic link between financial performance and financial equilibrium has rarely been studied in the long run for companies listed on the stock market. The present article fills this gap in the literature by examining the degree to which financial performance influenced long-term financial equilibrium using data from 34 major companies publicly traded on the New York Stock Exchange and operating around the world in a wide variety of industries and sectors. The period of analysis spread over a decade (2007Q1-2020Q3) in order to cover two major crises that have marked the dawn of the third millennium and occurred relatively close to one another: the 2008 financial meltdown and the COVID-19 pandemic crisis. By means of panel data modelling, the study showed that the short-term and long-term financial equilibria of these public companies measured by current ratio, quick ratio and debt to equity ratio were significantly impacted by different financial performance indicators. The study addresses various implications of the empirical results and lays out avenues for future research.
Keywords: 330; stock market; liquidity; performance; crises; solvency